Role of Advertising In the Development of Brand Image With Reference to Insurance Industry: A comparative analysis of advertising impact on brand image in the insurance industry (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The research study is done with reference to insuranceindustry. Three companies are taken for the study, first one is LIC, second isICICI Prudential and third one is ING Vysya life insurance. The impact ofadvertising message was seen on the brand image of these companies. Six printads were taken for each company and data was collected from five hundred andforty respondents and forming a sample size of thirty. Three questionnaireswere prepared one for brand image before showing advertising; second one foradvertising message and third one for brand image after showing ads. Throughthis study these three companies were also compared on the ground of whichcompany has the effect on its brand image by showing ads of that company beforeand after.